Problem #1: Infinity and infinity combined

Calculus Level 4

f ( k ) = n = 1 1 n ( n + 1 ) ( n + 2 ) ( n + k ) , f(k)=\sum_{n=1}^{\infty}\frac{1}{n(n+1)(n+2)\cdots(n+k)},

For positive integer k k , f ( k ) f(k) is defined as above. Then n = 5 n ( n 1 ) f ( n ) = p q \displaystyle \sum_{n=5}^{\infty} n(n-1)f(n) = \frac{p}{q} , where p p and q q are coprime positive integers. Find the value of p 2 + q 2 p^2+q^2 .


This problem is a part of the series <Advanced Problems> .


The answer is 577.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Boi (보이)
Oct 17, 2018

Since

1 n ( n + 1 ) ( n + 2 ) ( n + k ) = 1 k ( 1 n ( n + 1 ) ( n + 2 ) ( n + k 1 ) 1 ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + k ) ) \frac{1}{n(n+1)(n+2)\cdots(n+k)}=\frac{1}{k}\left(\frac{1}{n(n+1)(n+2)\cdots(n+k-1)}-\frac{1}{(n+1)(n+2)(n+3)\cdots(n+k)}\right)

we may have

f ( k ) = n = 1 1 k ( 1 n ( n + 1 ) ( n + 2 ) ( n + k 1 ) 1 ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + k ) ) = 1 k k ! f(k) = \sum_{n=1}^{\infty} \frac{1}{k}\left(\frac{1}{n(n+1)(n+2)\cdots(n+k-1)}-\frac{1}{(n+1)(n+2)(n+3)\cdots(n+k)}\right) = \frac{1}{k\cdot k!}

Hence

n = 5 n ( n 1 ) f ( n ) = n = 5 n 1 n ! = n = 5 ( 1 ( n 1 ) ! 1 n ! ) = 1 24 . \sum_{n=5}^{\infty} n(n-1)f(n) \\ = \sum_{n=5}^{\infty} \frac{n-1}{n!} \\ =\sum_{n=5}^{\infty}\left(\frac{1}{(n-1)!}-\frac{1}{n!}\right) \\ =\frac{1}{24}.

Therefore, p 2 + q 2 = 1 2 + 2 4 2 = 577 . p^2+q^2 = 1^2+24^2 = \boxed{577}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...